Multifunctional FeS2@SRF@BSA nanoplatform for chemo-combined photothermal enhanced photodynamic/chemodynamic combination therapy. (1st December 2021) - Feng, Miao; Li, Meiting; Dai, Rui; Xiao, Shuting; Tang, Junjie; Zhang, Xiaoge; Chen, Baizhu; Liu, Jie
Abstract : A FeS2 @SRF@BSA nanoplatform was established for chemo-combined PTT enhanced PDT/CDT to achieve an "all-in-one" therapeutic agent. The designed nanoplatform greatly inhibited the tumor growth and achieved sufficient in vivo antitumor efficacy. Abstract : Combination therapy has been widely studied due to its promising applications in tumor therapy. However, a sophisticated nanoplatform and sequential irradiation with different laser sources for phototherapy complicate the treatment process. Unlike the integration of therapeutic agents, we report a FeS2 @SRF@BSA nanoplatform for the combination of chemo-combined photothermal therapy (PTT) enhanced photodynamic therapy (PDT) and chemodynamic therapy (CDT) to achieve an "all-in-one" therapeutic agent. Ultrasmall FeS2 nanoparticles (NPs) with a size of 7 nm exhibited higher Fenton reaction rates due to their large specific surface areas. A photodynamic reaction could be triggered and could generate 1 O2 to achieve PDT under 808 nm irradiation. FeS2 NPs also exhibited the desired photothermal properties under the same wavelength of the laser. The Fenton reaction and photodynamic reaction were both significantly improved to accumulate more reactive oxygen species (ROS) with an increase of temperature under laser irradiation. Besides, loading of the chemotherapeutic drug sorafenib (SRF) further improved the efficacy of tumor treatment. To realize long blood circulation, bovine serum albumin (BSA) was used as a carrier to encapsulate FeS2 NPs and SRF, remarkably improving the biocompatibility and tumor enrichment ability of the nanomaterials. Additionally, the tumors on mice treated with FeS2 @SRF@BSA almost disappeared under 808 nm irradiation. To sum up, FeS2 @SRF@BSA NPs possess good biocompatibility, stability, and sufficient therapeutic efficacy in combination therapy for cancer treatment. Our study pointed out a smart design of the nanoplatform as a multifunctional therapeutic agent for combination cancer therapy in the near future.